DAMPAK PANDEMI COVID-19 TERHADAP KEMISKINAN DIKOTA KUPANG: ANALISIS TENTANG POLA KONSUMSI DAN MATA PENCAHARIAN MASYARAKAT PERKOTAAN DI MASA KRISIS - Sakera, Gabriela; Bulu, Yacobin; Laka, Natalia; Susu, Urbaningsi; Sel, Yohana; Lawalu, Tuti (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2025)
The COVID-19 pandemic has had a profound impact on the social and economic conditions of urban communities in Kupang City, particularly in terms of declining income and shifting consumption patterns. This study aims to examine the effects of the pandemic on poverty by focusing on two main aspects: changes in household consumption and the loss of livelihoods. Using a descriptive qualitative method, data were collected through interviews with local MSME actors and residents. The findings indicate that many small business owners suffered significant income losses, while the general population shifted their spending priorities toward basic necessities. In response, MSME actors sought to adapt by utilizing digital platforms and exploring alternative income sources. Despite government assistance efforts, the support was deemed insufficient for long-term needs. The study highlights the urgency of strengthening local economic resilience, supporting the informal sector, and accelerating MSME digitalization as key strategies for coping with future crises.